2010
DOI: 10.1159/000320906
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Pre-Screening Is More Sensitive in Liquid-Based Cytology than in Conventional Smears

Abstract: Rapid pre-screening (RPS) is a useful tool to measure and improve performance in the cytology laboratory. Whether RPS is more or less effective in liquid-based cytology than in conventional smears is unknown. We compared the estimated sensitivity in a laboratory of 11 cytotechnologists which converted from conventional smears to SurePath™ (Becton Dickinson, Franklin Lakes, N.J., USA) liquid based cytology. In the 9 months prior to conversion, 23,286 smears were screened compared with 30,610 smears in the 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The sensitivity of rapid prescreening was approximately 60% higher than that of 100% rapid review in detecting abnormalities as severe as ASC-US or worse, and although no other studies have yet been carried out to compare these methods, these findings are in agreement with other studies that have evaluated rapid prescreening and 100% rapid review separately. 3,4,9,19,20,[28][29][30][31][32] Significant improvement in sensitivity was found in routine screening following implementation of rapid prescreening and 100% rapid review as methods of internal quality control. Sensitivity increased 24% and 15% for rapid prescreening and 100% rapid review, respectively, in detecting abnormalities as severe as ASC-US or worse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity of rapid prescreening was approximately 60% higher than that of 100% rapid review in detecting abnormalities as severe as ASC-US or worse, and although no other studies have yet been carried out to compare these methods, these findings are in agreement with other studies that have evaluated rapid prescreening and 100% rapid review separately. 3,4,9,19,20,[28][29][30][31][32] Significant improvement in sensitivity was found in routine screening following implementation of rapid prescreening and 100% rapid review as methods of internal quality control. Sensitivity increased 24% and 15% for rapid prescreening and 100% rapid review, respectively, in detecting abnormalities as severe as ASC-US or worse.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,24,29,33 Rates of false-negative results of 1.80% and 1.14% identified by rapid prescreening and 100% rapid review, respectively, were consistent with those reported from other studies, in which the rate of false-negative results ranged from 0.0% to 9.8% with rapid prescreening and from 1.07% to 33.1% with 100% rapid review. 9,15,20,28,[34][35][36][37][38] What, then, would explain that one method is more sensitive than the other despite both methods using the same rapid-screening technique? Why was sensitivity higher in some studies evaluating the 100% rapid review method compared with others that evaluated the same technique?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not involve "rapid" prescreening, although there are tremendous advantages to that technique. [12][13][14][15] What we are proposing is that a random percentage of the laboratory's workload is prescreened in the usual fashion by cytotechnologists to identify abnormal cases, but no marks are made on the slides. Instead, the cytotechnologist goes to the LIS and enters in a prescreen diagnosis that then remains hidden until the time the case is signed out.…”
Section: Introductionmentioning
confidence: 99%